Chewing Side Preference, Facial Asymmetry and Related Factors in the Northern Finland Birth Cohort 1986 - Elina V. Heikkinen; Ville Vuollo; Tuomo Heikkinen; Virpi Harila (Medical Journals Sweden, 2024)
Objective: The aim of this study was to find out how the preferred chewing side (PCS) affects facial asymmetry, what kind of factors affect PCS, and whether there are differences in facial asymmetry between symmetrical and asymmetrical masticators. Material and Methods: The study included 748 subjects (females n=452, males n=296) born in 1985-1986 in Northern Finland (Northern Finland Birth Cohort 1986, NFBC 1986). Subjects' faces were captured in facial 3D images with stereophotogrammetry technology, and they filled in a questionnaire concerning oral health. A comprehensive dental examination was done by a dentist. Subject´s chewing side preference was studied by chewing a piece of paraffin, cotton roll or parafilm. Asymmetry was measured from 3D images with different asymmetry measurements and facial landmarks. Results: Reduced number of teeth on contralateral side affects PCS (OR = 2.44 in the case of one tooth is missing). Being female increased the whole face and lower face symmetry (p values <0.001-0.824). Self-reported TMD pain has an effect on the sidedness of the chin; there is more pain in the larger side of the chin (OR = 9.45). Different chewing materials had no significant effect on the proportion of chewing sides. Conclusions: Females have a more symmetrical face compared to males. PCS does not have a statistically significant effect on facial asymmetry, but the variable affecting PCS itself is extracted teeth.